Implementansi Model Knowledge Management System Pada Pelayanan Sertifikasi Algoritma - Retno Wulandari; Reva Ragam Santika; Yudi Wiharto; Ari Saputro (Universitas Budi Luhur, 2021)
Algorithm certification is a mandatory activity for students of the Information Technology Faculty at Budi Luhur University before their take final assignments and is managed by the faculty secretariat as a service unit for algorithm certification. Currently, Knowledge in algorithm certification services still relies on the ability of one person, so that if there any change of manager will cause the loss of explicit and tacit knowledge because they have no knowledge management which can help the manager to collect Knowledge to continue the management of algorithm certification. The purpose of this study is to make a proposed Knowledge Management model as a knowledge management center for algorithmic certification management for facilities for documenting, discussing, utilizing knowledge according to institutional regulations, and creating applications that can manage knowledge and share related to algorithmic certification activity services. This study uses the Tiwana framework model, and the method of scoring the results of system testing using Likert scale measurements, Forum Group Discussion (FGD), as a system prototype testing using the ISO 9126 method. The results of the analysis will produce a model and knowledge management system that is can be a solution in documenting and exchanging knowledge in applications to the algorithm certification unit.